Glomus Tumor of the Stomach: Depiction by Multidetector CT and Three-Dimensional Volume Rendering Imaging - Tarak H. Patel; Karen M. Horton; Ralph H. Hruban; Elliot K. Fishman (Case Reports in Medicine)
Glomus tumors are uncommon tumors which can occur anywhere within the gastrointestinal tract but have been shown to occur most commonly in the gastric antrum. On CT, these tumors demonstrate hyperenhancement which may help distinguish them from other gastric masses.